Opportunities and Challenges of Using Fintech in Takaful Financial Services - Faqih, Rijalul; Nurhayati, Nurhayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Fintech is currently part of the development of takaful, the results of research and studies related to this problem are still very limited, on the other hand all financial services industries are starting to shift to fintech, including the Islamic financial services industry. So it is necessary to explore the potential use of fintech in the sharia insurance industry, especially in terms of opportunities and challenges in the future. In particular, big data analytics and robo-advisory are explored and how takaful operators can combine them for better customer experience and gathering competitive intelligence. To stay competitive in a rapidly changing business environment, takaful operators need to identify and adopt fintechs that can positively impact customer experience and optimize cost efficiency.